A study on the implementation of Encoded Archival Description on the card catalog system of the Philippine Collegian issues from 1991 to 2000 - Garais, Angela C. (2010)
This study was geared towards the justification of the need for implementation of Encoded Archival Description on the existing card catalog system of the Philippine Collegian issues from 1991 to 2000. Encoded Archival Description is a recently established standard in encoding archival finding aids. In order to fulfill the objectives of this study, the researcher gathered information through face-to-face interviews with the personnel of the UP University Archives and Records Depository and through distribution of survey questionnaires and document analysis. Data gathered were analyzed and used in the implementation of Encoded Archival Description.